LO89: Factors associated with delay in trauma team activation and impact on patient outcomes. (15th May 2017) - Connolly, R.; Woo, M.; Lampron, J.; Perry, J.J.
Abstract : Introduction: Trauma code activation is initiated by emergency physicians using physiologic and anatomic criteria, mechanism of injury and patient demographic factors in conjunction with data obtained from emergency medical service personnel. This enables rapid definitive treatment of trauma patients. Our objective was to identify factors associated with delayed trauma team activation.Methods: We conducted a health records review to supplement data from a regional trauma center database. We assessed consecutive cases from the trauma database from January 2008 to March 2014 including all cases in which a trauma code was activated by an emergency physician. We defined a delay in trauma code activation as a time greater than 30 minutes from time to arrival to trauma team activation. Data were collected in Microsoft Excel and analyzed in Statistical Analysis System (SAS). We conducted univariate analysis for factors potentially influencing trauma team activation and we subsequently used multiple logistic regression analysis models for delayed activation in relation to mortality, length of stay and time to operative management.Results: 1020 patients were screened from which 174 patients were excluded, as they were seen directly by the trauma team. 846 patients were included for our analysis. 4.1% (35/846) of trauma codes were activated after 30 minutes. Mean age was 40.8 years in the early group versus 49.2 in the delayed group p=0.01. There was no significant difference in type of injury, injury severity or time from injury between the two groups. Patients were over 70 years in 7.6% in the early activation group vs 17.1% in the delayed group (p=0.04). 77.7% of the early group were male vs 71.4% in the delayed group (p=0.39). There was no significant difference in mortality (15.2% vs 11.4% p=0.10), median length of stay (10 days in both groups p=0.94) or median time to operative management (331 minutes vs 277 minutes p=0.52).Conclusion: Delayed activation is linked with increasing age with no clear link with increased mortality. Given the severe injuries in the delayed cohort which required activation of the trauma team further emphasis on the older trauma patient and interventions to recognize this vulnerable population should be made. When assessing elderly trauma patients emergency physicians should have a low threshold to activate trauma teams.